Removal of cadmium from aqueous solution using waste shells of golden apple snail. Issue 50 (26th October 2016) - Zhao, Benliang; Zhang, Jia-en; Yan, Wenbin; Kang, Xiaowu; Cheng, Chaogang; Ouyang, Ying
Abstract: Golden apple snail (GAS) is one of the 100 worst invasive alien species. With the application of molluscicides to kill and control the spreading of these snails, a large amount of dead GAS shells are remained in many farms. This study ascertained the characteristics and removal of cadmium (Cd) by the GAS shell (GASS) powders and the associate mechanisms. Results showed that when the concentration of shell powder increased from 0.05 to 10.00 g/L, pH from 1.5 to 5.5, contact time from 2 to 100 min, and temperature from 10 to 50°C, the Cd removal efficiency from the solution increased gradually and reached an equilibrium condition. The Cd removal efficiency decreased as the initial Cd concentration increased from 5 to 500 mg/L. The changes in the amount of Cd removal conformed to the Langmuir model with a capacity of 81.301 mg/g. A thermodynamic analysis indicated that the Cd removal by the GASS powder was an endothermic and spontaneous process. Our study also revealed that the solution pH was affected greatly by the amount of GASS powder. The powder X-ray diffractometer (XRD) and scanning electron microscopy indicated that the CdCO3 precipitated on the surface of GAS shells. The Cd removal was related to the ion exchange and the micro-precipitation with a depletion of aragonite and calcite. This study suggests that shells of GAS could be used as an effective biomaterial for Cd removal from contaminated water.